1966
DOI: 10.1364/ao.5.000051
|View full text |Cite
|
Sign up to set email alerts
|

Stresses Developed in Optical Film Coatings

Abstract: The development of stress in evaporated dielectric and metal films, used as optical coatings, has been investigated experimentally by observing the bending of a thin silica strip as it becomes coated. The strip forms one mirror of a laser interferometer mounted within the coating chamber, giving high measurement sensitivity. Stress data on a number of materials commonly used in coating are presented, and the behavior of multilayer coatings investigated. Analysis of the effect of film stress upon the figure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

1976
1976
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(47 citation statements)
references
References 4 publications
3
43
0
1
Order By: Relevance
“…An initial increase and the saturation of Dd=d with the film thickness observed in Fig. 2 agrees well with a similar trend for ZnS and CdTe films on silica substrates [9]. In the same report MgF 2 and CeF 3 also exhibit similar behavior.…”
Section: Resultssupporting
confidence: 86%
“…An initial increase and the saturation of Dd=d with the film thickness observed in Fig. 2 agrees well with a similar trend for ZnS and CdTe films on silica substrates [9]. In the same report MgF 2 and CeF 3 also exhibit similar behavior.…”
Section: Resultssupporting
confidence: 86%
“…Fig. 4 shows the relationship between the Cr film thickness and the internal stress determined by Ennos [10], together with our data, which qualitatively correspond to the former. Our experimental results show that Cr f'tim 68nm thick exhibits an internal tensile stress of 863 MNm -2 , which is the same order as the difference between the measured and calculated strengths in Fig.…”
Section: Methodssupporting
confidence: 82%
“…To explain this discrepancy, the internal stress in as-deposited Cr film was estimated, because Ennos [10] reported that the vacuum-deposited Cr film possesses a high internal tensile stress. The *Corning No.…”
Section: Methodsmentioning
confidence: 99%
“…The former is minimized by avoiding any color-dependent optical elements. For the latter, mechanical stress (specific to coating process), aging, and lightinduced damage (mostly from high power lasers) are known to alter the reflectance of the mirror over time (Ennos 1966;de Denus-Baillargeon et al 2014). With an FP housed in a thermally controlled evacuated chamber, we believe dispersion vari-A&A proofs: manuscript no.…”
Section: The Fpi Transmission Spectrummentioning
confidence: 99%